Fabrication and development of SPEEK/PVdF-HFP/SiO2 proton exchange membrane for microbial fuel cell application - Jagdeep Kumar Nayak; Uday Shankar; Kundan Samal (Chemical Engineering Journal Advances, 2023)
This study presents the potential of sulfonated poly (ether-ether-ketone)/ poly (vinylidene fluorideco-hexafluoro propylene)/SiO2 (SPEEK/PVdF-HFP/SiO2) composite proton exchange membrane for the use of microbial fuel cell. Silica particles (SiO2) were admixed with SPEEK/PVdF-HFP with various ratios. Scanning electron microscope (SEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Thermal Gravimetric Analysis (TGA) and Differential Scanning Calorimetric (DSC) were examined for characterizing the PEM membrane. Proton conductivity, oxygen diffusivity, ion exchange capacity (IEC), water uptake and performance for polymer composites using MFCs were analysed. The highest proton conductivity value of 8 × 10−2 S cm−1 was obtained for the SiO2–7.5 wt.% incorporated polymer membrane of SPEEK (80 wt.%) / PVdF-HFP (20 wt.%). The maximum voltage generation and power density of 998.5 ± 2 mV and 1.5 mW/m2 were noticed, respectively. This study suggests that the incorporation of SiO2 in polymer composite membrane has potential for an alternative PEM.